2014
DOI: 10.15171/ijhpm.2014.63
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence and Determinants of Under-Nutrition Among Children Under Six: A Cross-Sectional Survey in Fars Province, Iran

Abstract: The prevalence of under-nutrition in the study population was categorized in low levels. However, planning the public preventive strategies can help to control childhood under-nutrition according to underlying factors of malnutrition in the study population including gender, settlement area, family size, ethnicity, family income, maternal education, health services, and also safe water supply.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

40
117
7
6

Year Published

2016
2016
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 144 publications
(170 citation statements)
references
References 13 publications
40
117
7
6
Order By: Relevance
“…In the present study prevalence of children who were underweight was found to be higher among children attending urban anganwadi centres and these results were similar to a study done by Kavosi et al 13 , whereas other studies showed that prevalence of underweight is higher in rural areas. [14][15][16] Prevalence of stunting in our study was higher among children living in urban areas which was similar to a study done by Kavosi et al 13 In contrary other studies showed that the prevalence of stunting is higher in rural areas.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…In the present study prevalence of children who were underweight was found to be higher among children attending urban anganwadi centres and these results were similar to a study done by Kavosi et al 13 , whereas other studies showed that prevalence of underweight is higher in rural areas. [14][15][16] Prevalence of stunting in our study was higher among children living in urban areas which was similar to a study done by Kavosi et al 13 In contrary other studies showed that the prevalence of stunting is higher in rural areas.…”
Section: Discussionsupporting
confidence: 92%
“…Among those who were severely underweight 51.9% (14) were males and 48.1% (13) were females. This difference was not statistically significant (p= 0.284).…”
Section: Resultsmentioning
confidence: 99%
“…In comparison with the results of the present study, children's status has worsened from 1998 to 2015. However, this is still of better status compared with the status of the children from Cameroon, Peru, and Haiti (5,(14)(15)(16). In addition, the malnutrition status of children in Shahroud in the present time was found to be in a more unfavorable position than those from poor regions of China (17).…”
Section: Discussionmentioning
confidence: 60%
“…There was a dissimilarity between these findings and the present study findings. A cross-sectional community-based survey [21] was conducted among 15408 children under 5 years of age in Iran. The rates of stunting, underweight, and wasting were 9.53%, 9.66% and 8.19%, respectively.…”
Section: Discussionmentioning
confidence: 99%